TEAK SEEDS (Tectona grandis L.f.) GERMINATION BASED ON DIFFERENT CONCENTRATION AND SOAKING TIME LENGTH USING SULFURIC ACID SOLUTION (H2SO4) - Benu, Yakub; Kurra, Richardus Ghudi; Purba, Mahardika Putra; Manek, Luisa Moi; Aryani, Ni Kade Ayu Dewi (Forestry Study Program University Of Mataram, 2024)
Teak (Tectona grandis L.f.) is a plant that produces raw materials for the wood industry, which is very popular due to its high quality and selling value. Procurement of teak seeds can be done in two ways: generatively and vegetatively. One problem in cultivating this plant is the inhibition of seed germination due to dormancy. Teak roots experience physical inactivity, namely tough skin. One technique that can be used to break seed dormancy is through chemical treatment. This study aims to determine the concentration of sulfuric acid (H2SO4) and the appropriate soaking time to break the teak seeds dormancy. This research was conducted for two months in the Permanent Nursery of the Department of Forestry, State Agricultural Polytechnic of Kupang, from 15 November 2022 until 15 January 2023. This study used a Completely Randomized Design (CRD) with two factors. The first factor was the concentration of a sulfuric acid solution (control: K0, 75% H2SO4: K1, 80% H2SO4: K2, and 85% H2SO4: K3). The second factor was the soaking time (T1: 45 minutes, T2: 50 minutes, and T3: 55 minutes). The two factors was combined to produce 12 treatment combinations as a whole. Each treatment was repeated three times and used ten seeds, so the total seeds used were 360 seeds. The results showed that there was an interaction between the concentration of sulfuric acid solution (H2SO4) with soaking time length, where the combination of 75% sulfuric acid (H2SO4) concentration and 45 minutes of soaking time gave higher results than other treatments, so it can be said that this combination is better at breaking teak seed dormancy.